Rekonstruksi Tafsir Al-Quran Kontemporer (Studi Analisis Sumber dan Metode Tafsir) - Irsyadunnas Irsyadunnas; Nurmahni Nurmahni (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2020)
One of the weaknesses of the classical tafseer (interpretation) method is the lack of concern of the mufassir (quran interpreter) to the context of the verse, therefore, their interpretations tend to be asocial or ahistorical. This paper offers a reconstruction of methods and sources of interpretation which resulted in a form of interpretation that is pertinent to the development of science and society. In interpretation study, it is necessary to have a balance in three aspects: text, context, and perspective. It should also involve three elements in coincide, namely, asbãb al-nuzûl (the occasion of revelation), language analysis, and Weltanschaung analysis or world view.Abstrak: Salah satu kelemahan metode tafsir klasik adalah kurangnya perhatian mufasir terhadap konteks sebuah ayat, sehingga melahirkan tafsir yang cenderung asosial atau ahistoris. Tulisan ini menawarkan sebuah konstruksi metode dan sumber tafsir yang bisa menghasilkan sebuah tafsir yang relevan dengan perkembangan ilmu pengetahuan dan masyarakat. Dalam kajian tafsir perlu adanya keseimbangan dalam tiga hal yakni teks, konteks dan perspektif. Di samping itu juga harus melibatkan tiga unsur secara bersamaan, yakni asbãb al-nuzûl, analisis bahasa, dan analisis weltanschaung atau world view